Swedish Export Price Determination: Pricing to Market Shares? - Malin Adolfson (Sveriges Riksbank, 1999)
The Swedish export price determination for automobiles and kraft paper to three destination countries, over the period 1980-1994, is investigated. Formal tests on an error correction model indicate results consistent with price discrimination in Swedish exports of both goods. The exporters use their market power for pricing to market, which is characterized by the concern for foreign conditions, and implies an incomplete exchange rate pass-through. The pricing behaviour seems to be determined by the development of market shares, in about half of the cases. The total pass-through to the local currency price within a year, that is the effect of an exchange rate change working through all variables and all interactions in the price determination, span between -85 % and +111 %.
Keywords: E30; F31; F41; 330; Cointegration; Exchange rates; Export prices; Market shares; Pass-through; Pricing to market